Emerging Viral Pathogens: The Perpetual Challenge of Viral Emergence and Re-emergence - Singh, Ashutosh Kumar (Global Journal of Medical and Clinical Case Reports, 2025)
As the COVID-19 pandemic demonstrated, the continued emergence and spread of viral pathogens is a continuing global public health concern. This mini-review examines the factors contributing to the emergence and resurgence of viral pathogens and how viral agents, animal reservoirs, and human activities interact to facilitate the spread of new and emerging viruses. Recent research on the genetic plasticity of viruses - especially RNA viruses with high rates of mutation and recombination and recombination mechanisms that can lead to different variants infecting new hosts - is integrated into this strategy. It also recognises that the vast, largely unexplored reservoir of zoonotic viruses in wildlife, especially bats, rodents and non-human primates, is a source of spill-over effects and that anthropogenic drivers such as land use change, climate change, globalisation and urbanisation are accelerating the spread of pathogenic agents. Findings underscore that viral emergence is not a chance event. It is a predictable process caused by documented human, animal, and environmental interactions. This certainty demands an immediate and fundamental shift in global health strategy toward comprehensive solutions. These solutions must actively integrate proactive public health measures with greatly enhanced global surveillance networks. Also, it is necessary to have One-Health collaboration, the targeted ecosystem protection initiatives, and the investment in fast vaccine technology through platforms to be able to implement the successful mitigation. All these actions must be taken together to control future viral hazards and to challenge them successfully.